Etiology and complications of perforated peritonitis: a retrospective study - Balamaddiah, G.; Ravindranath, G. G. (International Surgery Journal, 2018)
Background: Peritonitis caused by perforation of the gastrointestinal tract is one of the most common emergencies in surgery and therefore required immediate recognition and management. The spectrum of this disease if different in India compared to the other parts of the world. Thus, this study was undertaken to assess the risk factors and outcome of this condition in the area. Methods: Forty-three patients, between 10-70 years, who had undergone treatment for perforated peritonitis either as an emergency or as an elective procedure were included into this retrospective study. Records of the inpatients were obtained from the medical records department of the hospital. Abdominal X-ray and abdominal and pelvic ultra sound was done for all the patients. Metronidazole and cefotaxime were given intravenously for all the patients. Records of the inpatients were obtained from the medical records department of the hospital. Results: Out of the 43 patients under study, 79% were males and 21% were females. The most predominant age group to be affected was 41-50 years followed by 51-60 years. 72.1% of the patients were alcohol users, 58.1% were smokers and 18.6% were on NSAIDs use. All the patients presented with abdominal pain and tenderness, followed by nausea and vomiting, presence of free fluid ad constipation. The most common cause for perforated peritonitis was peptic ulcers (58.1%), followed by enteric fever (16.3%), Tubercular peritonitis and ischemic bowel syndrome (7% each). Wound infections and electrolyte imbalance were the most common complications observed. Conclusions: Surgical peritonitis is one of the most common surgical emergency procedures performed. Since there is no way to prevent the peritonitis, the most effective treatment would be with the help of efficient and prompt surgery, with modern anesthesia and proper post-operative care. This would help to reduce the morbidity and mortality among the patients.